A Study on the Mass Spectrum of 2,3-Dihydro-4-Phenylthieno(2,3-b)Quinoline - Rajendran, S.P.; Shanmugam, P. (Asian Journal of Chemistry, 2010)
A study has been made on the fragmentation upon electron impact of 2,3-dihydro-4-phenylthieno(2,3-b)quinoline. As a dihydrothiophene, the molecular ion expels Ho, CS and CHSo species. Also, it eliminates H2, CH2S and SHo radicals. The first derived ions undergo further disintegration. The presence of 4-phenyl group causes 'Proximity effect' leading to the cyclisation of the daughter ions with the elimination of the elements of hydrogen.